2020
DOI: 10.1177/1937586720929044
|View full text |Cite
|
Sign up to set email alerts
|

The Appropriateness of Adapting the Australian Environmental Assessment Tool–High Care (EAT-HC) for Persons With Dementia in Singapore

Abstract: Objectives: This study investigated the level of acceptance in Singapore of the eight principles of design underpinning the Environmental Assessment Tool–High Care (EAT-HC), which is commonly used in Australia to evaluate environments for the care of people living with dementia. A secondary goal was to identify topics particularly relevant to the Singaporean context, which are not included in the Australian EAT-HC. Background: This study was undertaken in preparation for the development of a Singaporean versio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…The other two items, Items 5 and 64, dealing with the flooring of external environments and the need for familiar furniture refer to uncommon but desirable features in nursing homes in Singapore. While the psychometrics could be improved by the exclusion of these items, their educational function is considered to be very important (Sun & Fleming, 2018; Sun, 2020). Participants indicated that the SEAT was an important innovation, especially in aged care, and despite coming from a range of occupational backgrounds, they indicated that the tool is aligned with their goals of improving aged care, can be learned quickly, and is potentially useful to them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other two items, Items 5 and 64, dealing with the flooring of external environments and the need for familiar furniture refer to uncommon but desirable features in nursing homes in Singapore. While the psychometrics could be improved by the exclusion of these items, their educational function is considered to be very important (Sun & Fleming, 2018; Sun, 2020). Participants indicated that the SEAT was an important innovation, especially in aged care, and despite coming from a range of occupational backgrounds, they indicated that the tool is aligned with their goals of improving aged care, can be learned quickly, and is potentially useful to them.…”
Section: Discussionmentioning
confidence: 99%
“…The SEAT is an adaptation of the EAT-HC. The adaptation was based on the views of 150 participants (caregivers of people living with dementia, clinicians, care staff, design and aged care administrators, and policy makers) who took part in 23 focus groups discussion about the relevance of the principles of design and the content of the individual items (Sun, 2020). Results from the thematic analysis revealed a high level of acceptance of the applicability of the design principles and the content of the individual items and resulted in the development of six additional items for the SEAT bringing the total items from 77 items in the original EAT-HC to 83 items used in the first stage of testing.…”
Section: Assessment Toolsmentioning
confidence: 99%
“…Based on this study results, we plan to modify EAT-HC by adapting to cultural aspects of Japan. Developing an environmental assessment instrument with cultural adaptation would set higher expectations for the residents' QOL (Sun, 2020). Our next step is to translate the EAT-HC handbook to clarify the meaning of each question before applying it to small-scale dementia-care facility design.…”
Section: Limitation and Implicationsmentioning
confidence: 99%
“…Background information was added to describe the meaning of the question in more detail. This necessity is also pointed out by Sun (2021) and Brennan and colleagues (2021), who emphasize the different literacy levels of staff of facilities using the instrument to collect data [38]. Even for other instruments that depict the built environment, additional information is provided in manuals to address the difficulties of this difficult-to-capture construct [39][40][41].…”
Section: Enhancing Understanding Of the Dementia-specific Designmentioning
confidence: 99%